The prospects of biodegradable magnesium-based alloys in osteosynthesis - V. N. Chorny (Zaporožskij Medicinskij Žurnal)
In the analytical review of the literature the main stages of development of biodegradable magnesium alloys in surgery and traumatology were discussed. The analysis revealed the main problems: there is no way to control the speed of the biological resorption alloys, the effects of products of magnesium degradation on the tissues and the organism in general are not studied, there is no information on the characteristics of the regeneration of bone tissue when implanted magnesium implanted magnesium alloys